Pengaruh Kedisiplinan Kerja Dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai Di Badan Pangan Nasional: The Influence of Work Discipline and Work Environment on Employee Job Satisfaction at the National Food Agency - Safna Oktaviana; Rosmita Rosmita (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the influence of work discipline & work environment on employee job satisfaction at the National Food Agency. A quantitative approach was used, with data collected through questionnaires distributed to 35 employees. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 31 to determine both partial and simultaneous effects. The results show that work discipline has a significant effect on job satisfaction, with a t-value of 5.098 > t- table 2.03. The regression coefficient of 0.487 indicates that an increase in work discipline improves job satisfaction by 48.7%. The work environment also significantly affects job satisfaction, with a t-value of 4.237, with a regression coefficient of 0.174. Simultaneously, work discipline & work environment significantly influence job satisfaction, as indicated by an F-value of 17.823 > F-table 3.29 and significance level < 0.001. The R Square value of 0.527 shows that these two variables explain 52.7% of the variation in employee job satisfaction.